“Tegodek-Godek dait Tetuntel-Tuntel”: Development of Digital Books to Strengthen Character Education for Elementary School Children - Nisha Ayu Dwi Sukazi; Khairun Nisa; Prayogi Dwina Angga (MASI Mandiri Edukasi, 2025)
The limited media of pictorial reading that raises local wisdom and the lack of application of character values in learning are problems that underlie the need to develop relevant and contextual media for students. This research and development aims to develop a digital folklore book of the Sasak tribe,